Mild Traumatic Brain Injury Produces Neuron Loss That Can Be Rescued by Modulating Microglial Activation Using a CB2 Receptor Inverse Agonist - Bu, Wei; Ren, Huiling; Deng, Yunping; Del Mar, Nobel; Guley, Natalie M.; Moore, Bob M.; Honig, Marcia G.; Reiner, Anton (Frontiers in Neuroscience, 2016)
We have previously reported that mild TBI created by focal left-side cranial blast in mice produces widespread axonal injury, microglial activation, and a variety of functional deficits. We have also shown that these functional deficits are reduced by targeting microglia through their cannabinoid type-2 (CB2) receptors using two-week daily administration of the CB2 inverse agonist SMM-189. CB2 inverse agonists stabilize the G-protein coupled CB2 receptor in an inactive conformation, leading to increased phosphorylation and nuclear translocation of the cAMP response element binding protein (CREB), and thus bias activated microglia from a pro-inflammatory M1 to a pro-healing M2 state. In the present study, we showed that SMM-189 boosts nuclear pCREB levels in microglia in several brain regions by 3 days after TBI, by using pCREB/CD68 double immunofluorescent labeling. Next, to better understand the basis of motor deficits and increased fearfulness after TBI, we used unbiased stereological methods to characterize neuronal loss in cortex, striatum, and basolateral amygdala (BLA) and assessed how neuronal loss was affected by SMM-189 treatment. Our stereological neuron counts revealed a 20% reduction in cortical and 30% reduction in striatal neurons bilaterally at 2-3 months post blast, with SMM-189 yielding about 50% rescue. Loss of BLA neurons was restricted to the blast side, with 33% of Thy1+ fear-suppressing pyramidal neurons and 47% of fear-suppressing parvalbuminergic (PARV) interneurons lost, and Thy1-negative fear-promoting pyramidal neurons not significantly affected. SMM-189 yielded 50-60% rescue of Thy1+ and PARV neuron loss in BLA. Thus, fearfulness after mild TBI may result from the loss of fear-suppressing neuron types in BLA, and SMM-189 may reduce fearfulness by their rescue. Overall, our findings indicate that SMM-189 rescues damaged neurons and thereby alleviates functional deficits resulting from TBI, apparently by selectively modulating microglia to the beneficial M2 state. CB2 inverse agonists thus represent a promising therapeutic approach for mitigating neuroinflammation and neurodegeneration.